2020
DOI: 10.1136/postgradmedj-2019-137202
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the current concepts in the management of arteriovenous malformations of the brain

Abstract: BackgroundThere is a lack of consensus in the management of arteriovenous malformations (AVMs) of the brain since ARUBA (A Randomised trial of Unruptured Brain Arteriovenous malformations) trial showed that medical management is superior to interventional therapy in patients with unruptured brain AVMs. The treatment of brain AVM is associated with significant morbidity.Objectives and methodsA review was done to determine the behaviour of brain AVMs and analyse the risks and benefits of the available treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 85 publications
0
20
0
2
Order By: Relevance
“…Cerebral arteriovenous malformations (AVMs) and arteriovenous fistulas (AVFs) are congenital or acquired diseases characterized by arteriovenous shunt (AVS), which is a direct communication between the arterial and venous circulation without the capillary bed [1,2]. Patients with AVS carry certain risks of hemorrhagic complications [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral arteriovenous malformations (AVMs) and arteriovenous fistulas (AVFs) are congenital or acquired diseases characterized by arteriovenous shunt (AVS), which is a direct communication between the arterial and venous circulation without the capillary bed [1,2]. Patients with AVS carry certain risks of hemorrhagic complications [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…14 It provides an increased level of control during injection as well as more complete obliteration of AVMs as compared to glue embolization. 14 Additionally, the improved ease of use offered by EVOH has allowed for more types of cases to be treated endovascularly. 14 When embolization is pursued, liquid embolic agents including cyanoacrylate and ethylene vinyl alcohol generally are chosen, but particles and coils also can be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The use of liquid embolization with EVOH in humans with brain AVMs has been well‐documented 14 . It provides an increased level of control during injection as well as more complete obliteration of AVMs as compared to glue embolization 14 . Additionally, the improved ease of use offered by EVOH has allowed for more types of cases to be treated endovascularly 14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been observed that the AVM nidus is composed of haemodynamically independent compartments. 1 Exact knowledge about the nidus of an AVM and the connected vessels is very important in AVM embolization. 2 Haemodynamic AVM compartments can have one or more separate feeding arteries and one or more draining veins, and multiple compartments can share the same venous drainage.…”
Section: Introductionmentioning
confidence: 99%